Iron Chelation in Murine Models of Systemic Inflammation Induced by Gram-Positive and Gram-Negative Toxins - Danielle Fokam; Kayle Dickson; Kiyana Kamali; Bruce Holbein; Patricia Colp; Ashley Stueck; Juan Zhou; Christian Lehmann (MDPI AG, 2020)
Iron is an essential element for various physiological processes, but its levels must remain tightly regulated to avoid cellular damage. Similarly, iron plays a dual role in systemic inflammation, such as with sepsis. Leukocytes utilize iron to produce reactive oxygen species (ROS) to kill bacteria, but pathologically increased iron-catalyzed ROS production in sepsis can lead to damage of host cells, multi-organ failure and death. Temporary reduction in bioavailable iron represents a potential therapeutic target in sepsis. This study investigates the effect of the novel iron chelator, DIBI, in murine models of systemic (hyper-)inflammation: C57BL/6 mice were challenged with toxins from Gram-positive (Staphylococcus aureus: lipoteichoic acid, peptidoglycan) and Gram-negative bacteria (Escherichia coli and Klebsiella pneumoniae: lipopolysaccharide). Intravital microscopy (IVM) was performed to assess immune cell activation and its impact on microvascular blood flow in vivo in the microcirculation of the gut. Plasma inflammatory mediators were measured via multiplex assay, and morphologic change in intestinal tissue was evaluated. DIBI treatment decreased leukocyte (hyper-)activation induced by Gram-positive and Gram-negative toxins. In some cases, it preserved capillary perfusion, reduced plasma inflammatory markers and attenuated tissue damage. These findings support the utility of DIBI as a novel treatment for systemic inflammation, e.g., sepsis.